2022
DOI: 10.3390/life12101573
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Low-Temperature-Treated Tetraploid Yellow Actinidia chinensis Planch. Tissue Culture Plantlets

Abstract: The cold-resistant mechanism of yellow kiwifruit associated with gene regulation is poorly investigated. In this study, to provide insight into the causes of differences in low-temperature tolerance and to better understand cold-adaptive mechanisms, we treated yellow tetraploid kiwifruit ‘SWFU03’ tissue culture plantlets at low temperatures, used these plantlets for transcriptome analysis, and validated the expression levels of ten selected genes by real-time quantitative polymerase chain reaction (RT-qPCR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Hence, finding genes or molecular markers related to the traits is vital for fruit tree breeding. Modern techniques, for example, transcriptome, proteomics, and genomics can help screen salt-tolerancerelated genes or molecular markers [2,7,8]. Combining cross-breeding with transcriptome sequencing technology to screen kiwifruit salt-tolerance-related genes is helpful for assisting in the breeding of salt-tolerant varieties [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, finding genes or molecular markers related to the traits is vital for fruit tree breeding. Modern techniques, for example, transcriptome, proteomics, and genomics can help screen salt-tolerancerelated genes or molecular markers [2,7,8]. Combining cross-breeding with transcriptome sequencing technology to screen kiwifruit salt-tolerance-related genes is helpful for assisting in the breeding of salt-tolerant varieties [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that kiwifruit, like other salt-intolerant species, exhibit slowed growth, yellowing of leaves, and even death under salt-stressed environmental conditions [11]. The study of tree transcriptomes enables us to obtain new insights into the genetic basis for the formation of tree traits [7,8,10]. The study of salt stress response in plants has become a hot topic, and transcriptomic analysis has identified metabolic pathways associated with salt stress, including plant hormone signal transduction [12], lignin synthesis [13], starch, and the sucrose metabolism pathway [14,15].…”
Section: Introductionmentioning
confidence: 99%